Application of B-Type Natriuretic Peptide in Neonatal Diseases - Xie, Haotai; Huo, Yixuan; Chen, Qinzheng; Hou, Xinlin (Frontiers in Pediatrics, 2021)
Numerous congenital or secondary diseases, including, heart disease, respiratory disease, sepsis and many others, can lead to neonatal death. B-type natriuretic peptide (BNP) is a peptide hormone secreted by ventricular cells following an increase in ventricular wall tension. BNP functions to promote vasodilation, diuresis, and sodium release to regulate blood pressure. BNP is a sensitive index reflecting ventricular function, which may aid the diagnosis and monitoring of various neonatal diseases. In neonates, there is currently no consensus on a reference BNP level, as the plasma BNP concentration of healthy newborns varies with age, peaks in the first week after birth, and then gradually decreased to a stable level. In disease states, the correlation between the plasma BNP concentration and the results of echocardiography is good, which is of great significance in the screening, monitoring, and prognosis evaluation of neonatal cardiovascular diseases, including congenital heart disease, patent ductus arteriosus, etcetera. It also facilitates the judgment of the efficacy of treatment and perioperative management. Moreover, the monitoring of plasma BNP concentration provides guidance for the diagnosis, evaluation, and treatment selection of certain neonatal respiratory diseases and neonatal sepsis. This review summarizes the normal BNP values and discusses the application value of BNP in relation to physiological and pathological aspects in neonates.